Microsurgical central lymphatic reconstruction—the role of thoracic duct lymphovenous anastomoses at different anatomical levels - Weinzierl, Andrea; Grünherz, Lisanne; Puippe, Gilbert Dominique; Gnannt, Ralph; von Reibnitz, Donata; Giovanoli, Pietro; Vetter, Diana; Möhrlen, Ueli; Wildgruber, Moritz; Müller, Andreas; Pieper, Claus Christian; Gutschow, Christian Alexander; et al. (Frontiers in Surgery, 2024)
In recent years advances have been made in the microsurgical treatment of congenital or acquired central lymphatic lesions. While acquired lesions can result from any surgery or trauma of the central lymphatic system, congenital lymphatic lesions can have a variety of manifestations, ranging from singular thoracic duct abnormalities to complex multifocal malformations. Both conditions may cause recurrent chylous effusions and downstream lymphatic congestion depending on the anatomical location of the thoracic duct lesion and are associated with an increased mortality due to the permanent loss of protein and fluid. We present a case series of eleven patients undergoing central lymphatic reconstruction, consisting of one patient with a cervical iatrogenic thoracic duct lesion and eleven patients with different congenital thoracic duct lesions or thrombotic occlusions. Anastomosis of the thoracic duct and a nearby vein was performed on different anatomical levels depending on the underlying central lymphatic pathology. Cervical (n=4), thoracic (n=1) or abdominal access (n=5) was used for central lymphatic reconstruction with promising results. In 9 patients a postoperative benefit with varying degrees of symptom regression was reported. Thus, the presented case series illustrates the current rapid advances in the field of central microsurgical reconstruction of lymphatic lesions alongside the relevant literature.